Political business cycles at the municipal level - Linda Veiga; Francisco Veiga (European Regional Science Association (ERSA), 2004)
The political article tests for rational political business cycles models on an unexplored and large data set of Portuguese municipalities. This data allows for a clean test of the models due to its high level of detail on expenditure items, an exogenous fixed election schedule and the homogeneity of local governments with respect to policy instruments and institutions. Estimation results clearly reveal the opportunistic behaviour of local governments, that in pre-electoral periods, increase expenditure on items highly visible to the electorate such as roads and street construction, in an effort to signal competence and increase their chances of re-election. JEL classification: H72, D72, D78 Keywords: political business cycles, public finance, local governments
Keywords: H72; D72; D78; 330; political business cycles; public finance; local governments